Implikasi Ekonomi UU Telekomunikasi Nomor 36 Tahun 1999 dan Ekosistem Komunikasi Digital - Muhamad Agung Dharmajaya; Muhamad Isnan Nur Ikhwan; Fajri Syahiddinillah; Harmonis Harmonis (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Telecommunications is important in the current era because it allows people to connect with each other and access information and services easily and quickly. The aim of this research is to analyze the economic implications of the Universal Access Telecommunications Law on regulatory review and its impact on the digital communications ecosystem. This study used qualitative research methods. The data collection technique in this research uses the literature study method. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that telecommunications inequality is one of the challenges in efforts to advance the nation through information and communication technology innovation, while the right to obtain telecommunications is a right that every Indonesian citizen has. In Law no. 36 of 1999, in article 16 there are regulations regarding the implementation of universal access, universal service is a policy that aims to ensure the availability of telecommunications services and internet access that is equitable and affordable for all communities, especially poor and remote communities.